Deciphering Activity in Early Facial Vitiligo: A Case Report Integrating Clinical, Wood's Lamp, and Dermoscopic Findings - Rina Gustia; Mutia Sari; Afifah Alfyanita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The management of non-segmental vitiligo hinges on accurately assessing disease activity to guide appropriate therapy. A clinical challenge arises in patients presenting with a low vitiligo area scoring index (VASI), suggesting limited disease, which may be discordant with underlying inflammatory activity, potentially leading to therapeutic inertia. Case presentation: A 34-year-old woman with Fitzpatrick skin type III presented with a two-month history of rapidly progressing facial vitiligo, preceded by an erythematous phase. Despite a low VASI score of 1, the patient-reported vitiligo disease activity (VIDA) score was +4. Dermoscopy was instrumental, revealing definitive in-vivo evidence of inflammation and instability, including a pinkish background, telangiectasias, and a reversed pigment network. Based on this discordance between disease extent and activity, a multi-modal therapeutic regimen was initiated. A six-month follow-up demonstrated disease stabilization and significant perifollicular repigmentation, with resolution of the inflammatory dermoscopic signs. Conclusion: This case report illustrates the critical importance of an integrated diagnostic approach that moves beyond area-based assessment. It highlights how dermoscopy, when used to resolve the clinical paradox of low-extent but high-activity disease, can serve as an objective biomarker to justify timely and robust immunomodulatory intervention. This approach is crucial for altering the disease trajectory and optimizing patient outcomes.